2018
DOI: 10.7554/elife.29988
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of G2-M by ATR (mei-41)/Chk1(Grapes) facilitates tracheoblast growth and tracheal hypertrophy in Drosophila

Abstract: Imaginal progenitors in Drosophila are known to arrest in G2 during larval stages and proliferate thereafter. Here we investigate the mechanism and implications of G2 arrest in progenitors of the adult thoracic tracheal epithelium (tracheoblasts). We report that tracheoblasts pause in G2 for ~48–56 h and grow in size over this period. Surprisingly, tracheoblasts arrested in G2 express drivers of G2-M like Cdc25/String (Stg). We find that mechanisms that prevent G2-M are also in place in this interval. Tracheob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…These tracheoblasts remain quiescent through most of larval life and rekindle a mitotic program prior to pupariation. Tracheoblasts in the Dorsal Trunk (DT) in Tr2 enter larval life in G1, transition from G1 to S to G2 in the first larval instar (L1) and remain arrested in G2 from second instar (L2) till 32–40 hr into third larval instar (L3) whereupon they re-enter mitosis ( Figure 1A ; Kizhedathu et al, 2018 ). These cells express high levels of Chk1 mRNA and phosphorylated Chk1 (pChk1) during the period in which they are paused in G2 and downregulate levels of Chk1 mRNA and pChk1 upon mitotic re-entry.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These tracheoblasts remain quiescent through most of larval life and rekindle a mitotic program prior to pupariation. Tracheoblasts in the Dorsal Trunk (DT) in Tr2 enter larval life in G1, transition from G1 to S to G2 in the first larval instar (L1) and remain arrested in G2 from second instar (L2) till 32–40 hr into third larval instar (L3) whereupon they re-enter mitosis ( Figure 1A ; Kizhedathu et al, 2018 ). These cells express high levels of Chk1 mRNA and phosphorylated Chk1 (pChk1) during the period in which they are paused in G2 and downregulate levels of Chk1 mRNA and pChk1 upon mitotic re-entry.…”
Section: Resultsmentioning
confidence: 99%
“…Since perturbations in Wnt signaling led to precocious proliferation akin to the loss of Chk1, next we probed the role of Wnt pathway in Chk1 activation (phosphorylated Chk1, pChk1). pChk1 levels are high in tracheoblasts in L2 and early L3 and significantly lower at 32–40 h L3 ( Kizhedathu et al, 2018 ). pChk1 immunostaining in Btl-TCF RNAi at L2 showed that the levels of pChk1 were dramatically reduced in comparison to wild type ( Figure 2A , n = 6–8 tracheae per condition per experiment, n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations